2017
DOI: 10.13104/imri.2017.21.2.82
|View full text |Cite
|
Sign up to set email alerts
|

MR Findings of Seizure-Related Cerebral Cortical Lesions during Periictal Period

Abstract: Original ArticlePurpose: This study investigated the MRI, MR angiography (MRA) and MR perfusion findings of seizure-related cerebral cortical lesions during the periictal period. Materials and Methods: From a retrospective review of the institutional database between 2011 and 2014, a total of 21 patients were included in this study. Two radiologists assessed periictal MRI, including MRA and MR perfusion, in patients with seizure-related cortical lesions. The parameters examined include: location of cortical ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Postictal edema may be present in imaging done immediately after seizure episode or with status epilepticus. 33,34 In two patients of our series, isolated subcortical white matter edema was noted without any other findings (►Fig. 13).…”
Section: Postictal Edemamentioning
confidence: 73%
“…Postictal edema may be present in imaging done immediately after seizure episode or with status epilepticus. 33,34 In two patients of our series, isolated subcortical white matter edema was noted without any other findings (►Fig. 13).…”
Section: Postictal Edemamentioning
confidence: 73%
“…This creates a relative mismatch between consumption and delivery of metabolites 11 triggering reactive hyperperfusion to the brain region. 16 Eventually, the Na+/K+-ATPase pump fails, resulting in an influx of sodium ions and water into the neuron, causing cytotoxic edema. The cortex, with higher energy demands than the underlying white matter, shows preferential involvement, 17 while the white matter exhibits vasogenic edema, producing the split ADC sign.…”
Section: Discussionmentioning
confidence: 99%
“…However, Signh et al reported that restricted diffusion was found only 45.5% of reported patients. There has been no clear explanation of the MR signal changes related to the seizure [ 13 15 ]. However, restricted diffusion on MR is usually associated with acute cerebral infarction, neoplasms, intracranial infections, traumatic brain injury, and status with demyelination processes [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%